Mananoligossacarídeo em dietas para leitões desmamados - da Silva, Susana Zaneti [UNESP]; Thomaz, Maria Cristina [UNESP]; Watanabe, Pedro Henrique [UNESP]; Robles Huaynate, Rizal Alcides [UNESP]; Ruiz, Urbano dos Santos [UNESP]; Pascoal, Leonardo Augusto Fonseca [UNESP]; dos Santos, Vivian Maia [UNESP]; Masson, Guido Carlos Iselda Hermans [UNESP] (My University, 2012)
An assay was carried out to evaluate the use of mannanoligosaccharide (MOS) in piglet diets on performance, diarrhea incidence and blood parameters. Different levels of MOS inclusion (0, 0.1 and 0.2%) for pig diets were compared. A total of 72 piglets of Topigs lineage weaned at 21 days of age with 5.28±0.90 kg of live weight were used. It was used a randomized block design to control differences between initial weights of replicates. The results show that MOS inclusion in weaning pig diets did not promote better results on daily weight gain, daily feed intake and feed conversion. Although reduction in diarrhea incidence was observed in animals fed with 0.2% MOS diet, this prebiotic did not improve the immune response of piglets. Any level of MOS evaluated is recommended for piglets.
Mannanoligosacharide in diets for weaning pigs
Keywords: Diarrhea; Immunoglobulins; Post-weaning; Prebiotic; Sus scrofa; Animalia; Suidae